2012
DOI: 10.2215/cjn.10601011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Six versus Three Times per Week Hemodialysis on Physical Performance, Health, and Functioning

Abstract: SummaryBackground and objectives Relatively little is known about the effects of hemodialysis frequency on the disability of patients with ESRD.Design, setting, participants, & measurements This study examined changes in physical performance and selfreported physical health and functioning among subjects randomized to frequent (six times per week) compared with conventional (three times per week) hemodialysis in both the Frequent Hemodialysis Network daily (n=245) and nocturnal (n=87) trials. The main outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
92
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 56 publications
5
92
1
4
Order By: Relevance
“…In this context, one study demonstrated no significant difference in HRQOL of patients treated with nocturnal HD or peritoneal dialysis (PD), both of which were performed at home (50). Nevertheless, the short-daily in-center FHN trial suggests that selected HRQOL measures, such as the physical health composite score of the Short-Form 36, improved significantly, even though objective measurements of exercise tolerance did not improve (51). Of note, however, sustained improvements in patient-reported outcomes have been demonstrated in a variety of measures, including sleep, restless legs, depressive symptoms, time to recovery after an HD session, and almost all domains on the Short-Form 36 (34,35,52).…”
Section: Health-related Quality Of Life and Home Hdmentioning
confidence: 99%
“…In this context, one study demonstrated no significant difference in HRQOL of patients treated with nocturnal HD or peritoneal dialysis (PD), both of which were performed at home (50). Nevertheless, the short-daily in-center FHN trial suggests that selected HRQOL measures, such as the physical health composite score of the Short-Form 36, improved significantly, even though objective measurements of exercise tolerance did not improve (51). Of note, however, sustained improvements in patient-reported outcomes have been demonstrated in a variety of measures, including sleep, restless legs, depressive symptoms, time to recovery after an HD session, and almost all domains on the Short-Form 36 (34,35,52).…”
Section: Health-related Quality Of Life and Home Hdmentioning
confidence: 99%
“…Executive function and global cognition are not improved, although enhanced performance was found on tests of memory and verbal fluency (7). Self-reported physical health and functioning were improved but had no significant effect on objective physical performance (8). The FHN Group also reported on cardiac function (9,10), anemia (11), residual kidney function (12), and nutrition (13).…”
mentioning
confidence: 99%
“…As secondary outcomes, the FHN trial assessed the effect of frequent hemodialysis on physical performance, health, and functioning. The results are presented in this issue of CJASN by Hall et al (11).…”
mentioning
confidence: 89%